Quantitative determination of iron (III) in polymaltose haematinic formulations on the Ghanaian market - Rita Okwampah; Kofi Dzorgbenyuie Bedzra; Oti Kwasi Gyamfi; James Ataki; Foster Kyei; Martin Adarkwah-Yiadom; Edem Sosu; Emmanuel Boateng (PLoS ONE, 2025)
Iron is an essential element needed by living organisms to enable their bodies to perform a variety of cellular functions and it is tightly regulated in the body systems of living organisms. One major public health issue in developing countries is the problem of iron deficiency and iron deficiency anaemia in infants, young children, and adults. In sub-Saharan Africa, Ghana is one of the very few countries implementing a universal health insurance programme and therefore, iron (III) polymaltose complex suspension has been one of the medications on the National Health Insurance Scheme (NHIS) drug list. Studies conducted on iron (III) hydroxide with polymaltose in liquid dosage forms in certain parts of the world have been sub-standard. Consequently, this study aims to determine iron (III) in pharmaceutical formulations in some selected haematinics in syrups sold on the Ghanaian market. Seventeen (17) randomly selected products were analysed. Measurements were carried out at 628nm. Results obtained indicated that the concentration of iron (III) ranged between (45.3–49.2) mg/5mL and (57.9–83.4) mg/5mL. At a 95% confidence interval, the population mean of the concentration of the haematinic was between (54 mg/5mL - 66 mg/5mL). As much as anaemia can be cured with iron supplementation, excess iron overload can be very dangerous to the human body therefore Pharmaceutical products should be analysed on a regular basis to ensure their safety and effectiveness.